Applying a verification classification system to medical and forensic digital images. (May 2014) - Shapter, Michael
Abstract This paper gives the definitions, and describes the application, of a classification system for photographic veracity relating to medical and forensic images. It uses practical examples to demonstrate the reasons and parameters for using such a system. It also calls for continued discussion on what the limits and extent should be for the parameters. A debate encompassing the advantages and disadvantages of manipulating photographs goes back well before the introduction of digital imaging and has continued since the introduction of photography in the mid-nineteenth century. This author's first foray dates back twenty years1. The introduction of digital imaging only gave the debate new impetus and new problems to solve2, some of which might be resolved as suggested in this paper.